Self-help and village development: rural domestic water supplies in Lesotho - Cross, Edward Piers Woodrow (My University, 2015)
Situated within an analysis of regional underdevelopment the dissertation evaluates a self-help (or community development) rural development programme building water supplies in Lesotho. The social and material achievements of the programme are considered; social and cultural constraints to the acceptability and effectiveness of the programme are discussed; the implications of self-help strategy are investigated; and recommendations are made to improve management of the supplies. • The dissertation illustrates the use of an anthropological perspective in development planning, and is based on an evaluation commissioned in 1975 by the Governments of Lesotho and the United Kingdom. The basic material for the dissertation was gathered in the course of nine months residence in the mountainous Easternmost district of the country, Mokhotlong. Information was obtained by social anthropological fieldwork methods working in a total of fourteen villages. Results show the programme to have achieved very little. The immediate problems faced are an overstimulation of demand for supplies and the creation of a subs 'al backlog, and a high rate of breakdown among the supplies installed. The material benefits of the programme are minimal; there has been no change in domestic water use patterns and consequently little impact upon health; water quality has improved but this has